2020
DOI: 10.3390/genes11020221
|View full text |Cite
|
Sign up to set email alerts
|

AaCOI1, Encoding a CORONATINE INSENSITIVE 1-Like Protein of Artemisia annua L., Is Involved in Development, Defense, and Anthocyanin Synthesis

Abstract: Artemisia annua is an important medicinal plant producing the majority of the antimalarial compound artemisinin. Jasmonates are potent inducers of artemisinin accumulation in Artemisisa annua plants. As the receptor of jasmonates, the F-box protein COI1 is critical to the JA signaling required for plant development, defense, and metabolic homeostasis. AaCOI1 from Artemisia annua, homologous to Arabidopsis AtCOI1, encodes a F-box protein located in the nuclei. Expressional profiles of the AaCOI1 in the root, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Currently, as a polygenic family, the COI1 gene has been identified and reported in many plants, such as A. thaliana [ 31 ], O. sativa [ 18 ], Artemisia annua [ 51 ], T. aestivum [ 27 ], and Hevea brasiliensis [ 50 ]. In this study, a total of 156 COI1 proteins were identified from 19 land plant genomes, including 21 SsCOI1s from S. spontaneum , three ShCOI1s from R570, and seven SbCOI1s from S. bicolor , but no COI1 was obtained from five algae plants.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, as a polygenic family, the COI1 gene has been identified and reported in many plants, such as A. thaliana [ 31 ], O. sativa [ 18 ], Artemisia annua [ 51 ], T. aestivum [ 27 ], and Hevea brasiliensis [ 50 ]. In this study, a total of 156 COI1 proteins were identified from 19 land plant genomes, including 21 SsCOI1s from S. spontaneum , three ShCOI1s from R570, and seven SbCOI1s from S. bicolor , but no COI1 was obtained from five algae plants.…”
Section: Discussionmentioning
confidence: 99%
“…In the damage treatment of Aquilaria sinensis , AsCOI1 showed a high increase in expression at 1 h, about 20-fold higher, and the highest expression level at 6 h, about 33-fold higher [ 32 ]. In addition, the expression of AaCOI1 in the leaves of Artemisia annua was significantly upregulated 6 h after wounding [ 33 ]. SlCOI1 is essential for JA induced gene expression in tomatoes, and the JA signaling pathway with SlCOI1 as the co-receptor plays a different role in controlling the expression levels of early and late response genes in wounding responses [ 34 ].…”
Section: Discussionmentioning
confidence: 99%